Factors influencing HPV vaccine delivery by healthcare professionals at public health posts in São Paulo, Brazil. Issue 1 (11th November 2016) - Figueroa‐Downing, Daniella; Baggio, Maria Luiza; Baker, Misha L.; Dias De Oliveira Chiang, Ellen; Villa, Luisa L.; Eluf Neto, Jose; Evans, Dabney P.; Bednarczyk, Robert A.
Abstract: Objective: To assess the association between Brazilian healthcare providers' characteristics and their knowledge, perceptions, and practices regarding the HPV vaccine. Methods: An observational cross‐sectional study was conducted at five public health posts in São Paulo between July 28 and August 8, 2014. Healthcare professionals directly involved in patient care were asked to complete a written survey. Factors associated with routine verification of HPV vaccination status were evaluated using Poisson regression. Results: Among 200 participants included, 74 (38.5%) reported never and 70 (36.5%) reported always asking about HPV immunization status. Doctors were significantly less likely to report always asking than were community health agents (5/39 [12.8%] vs 32/60 [53.3%]; adjusted prevalence ratio [aPR] 0.25 [95% confidence interval (CI) 0.07–0.91]). Knowledge about the correct dosing schedule was associated with always rather than never verifying vaccination status (aPR 2.46 [95% CI 1.06–5.70]). Conclusion: Knowledge and attitude played secondary roles in influencing HPV vaccine verification. Community health agents were crucial for vaccine promotion; continued education and support of this group is essential for the sustained success of HPV immunization efforts in Brazil. Abstract : Community health agents are crucial for HPV vaccine promotion and essential for the sustained success of HPV immunization efforts in Brazil.